Distinct patterns of blood-stage parasite antigens detected by plasma IgG subclasses from individuals with different level of exposure to Plasmodium falciparum infections - Olesen, Cathrine H; Brahimi, Karima; Vandahl, Brian; Lousada-Dietrich, Susana; Jogdand, Prajakta S; Vestergaard, Lasse S; Dodoo, Daniel; Højrup, Peter; Christiansen, Michael; Larsen, Severin O; Singh, Subhash; Theisen, Michael (My University, 2010)
Abstract Background In endemic regions naturally acquired immunity against Plasmodium falciparum develops as a function of age and exposure to parasite infections and is known to be mediated by IgG. The targets of protective antibodies remain to be fully defined. Several immunoepidemiological studies have indicated an association of cytophilic anti-parasite IgG with protection against malaria. It has been hypothesized that the initial antibody responses against parasite antigens upon first few Plasmodium falciparum infections is dominated by non-protective IgG2/IgG4 and IgM antibodies, which then gradually develop into protective response dominated by cytophilic IgG1 and IgG3 antibodies. Methods Naturally occurring IgG antibodies against P. falciparum blood-stage antigens were analysed from plasma samples collected from four groups of individuals differing in age and level of exposure to P. falciparum infections. Western Blot profiling of blood-stage parasite antigens displaying reactivity with individual plasma samples in terms of their subclass specificities was conducted. Parasite antigens detected by IgG were grouped based on their apparent molecular sizes resolved by SDS-PAGE as high molecular weight (≥ 70 kDa) or low molecular weight (< 70 kDa). The number of discernable low molecular weight parasite antigens detected by different IgG subclass antibodies from each plasma sample was recorded. Using Wilcoxons rank sum test these reactivities were compared amongst groups of individuals with different levels of exposure to P. falciparum infections. Results IgG4 and IgM antibodies in plasma samples from all groups detected very few parasite antigens. IgG2 antibodies from all groups detected a common pattern of high molecular weight parasite antigens. Cytophilic IgG subclasses in plasma samples from individuals with higher levels of exposure to P. falciparum infections distinctly detected higher numbers of low molecular weight parasite antigens. Conclusions In the present study, there was no evidence for switching of antibody responses from non-cytophilic to cytophilic subclasses against blood-stage parasite antigens as a likely mechanism for induction of protective immunity against malaria.